2017
DOI: 10.1177/2054358117698667
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in Minimal Change Disease

Abstract: Treatment with rituximab, a monoclonal antibody against the B-lymphocyte surface protein CD20, leads to the depletion of B cells. Recently, rituximab was reported to effectively prevent relapses of glucocorticoid-dependent or frequently relapsing minimal change disease (MCD). MCD is thought to be T-cell mediated; how rituximab controls MCD is not understood. In this review, we summarize key clinical studies demonstrating the efficacy of rituximab in idiopathic nephrotic syndrome, mainly MCD. We then discuss im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 161 publications
(241 reference statements)
0
15
0
Order By: Relevance
“…MCD is thought to be T cell-mediated; thus, the role of rituximab in this disease is still unclear. Some published clinical studies have described the efficacy of rituximab in MCD in pediatric patients; however, its clinical role in adult patients remains undetermined [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…MCD is thought to be T cell-mediated; thus, the role of rituximab in this disease is still unclear. Some published clinical studies have described the efficacy of rituximab in MCD in pediatric patients; however, its clinical role in adult patients remains undetermined [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all studies showed that RTX was effective in the treatment of refractory NS in children, and it could Azarfar et al hypercholesterolemia (2). Approximately 20% of children do not respond completely and have steroid-resistant NS (SRNS), and 80%-90% of children with steroidsensitive nephrotic syndrome (SSNS) experience relapses.…”
Section: Discussionmentioning
confidence: 99%
“…According to the NS clinical guidelines, for the management of children who develop frequentlyrelapsing NS (FRNS) or steroid-dependent NS (SDNS), a low-dose alternate day steroid regimen, as the first-line treatment, is prescribed (1). Long-term glucocorticoid use in FRNS/SDNS patients leads to reduced bone mineral density, hypertension, increased infection risks, comorbidities such as cushingoid habitus, growth retardation, striae and acne, cataracts, pseudotumor cerebri, impaired glucose tolerance and hypercholesterolemia (2). Approximately 20% of children do not respond completely and have steroid-resistant NS (SRNS), and 80%-90% of children with steroid-sensitive NS (SSNS) experience relapses.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent relapses, steroid-dependence, or steroid-resistance require repeated courses of treatment ( 9 ). Thereby, high doses and long-term steroid treatments are needed, frequently leading to adverse effects and toxicity ( 1 , 13 ). Therefore, alternative immunosuppressive treatments are applied in these patients, including alkylating agents, calcineurin inhibitors, mycophenolate mofetil, and rituximab ( 1 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, CD20 is not expressed on human podocytes ( 18 ). Depletion of CD20 expressing cells using rituximab has shown promising results in the treatment of MCD ( 10 , 13 , 19 , 20 ), leading to the hypothesis that B cells have a pathogenetic role in MCD. Nonetheless, the precise mechanisms of action of rituximab in the treatment of MCD are unknown ( 9 , 21 ).…”
Section: Introductionmentioning
confidence: 99%